DAMPAK PEMINDAIAN IBU KOTA TERHADAP POTENSI PARIWISATA DI KALIMANTAN TIMUR - Dananjaya, Ahmad Ghazy (TEHBMJ (Tourism Economics Hospitality and Business Management Journal), 2025)
This study critically examines the profound implications of Indonesia's capital city relocation to Ibu Kota Nusantara (IKN) in East Kalimantan, particularly its multifaceted impact on regional tourism. While the official narrative frames IKN as a catalyst for "Indonesia-centric" development and a "green, smart, and sustainable forest city" bolstered by ambitious city branding, our findings highlight significant paradoxes and inherent risks. The promise of economic equity from the "Indonesia-centric" narrative risks manifesting as an isolated development "bubble," and the noble environmental vision could become "greenwashing" if massive construction proceeds without stringent mitigation and transparency. Similarly, potent city branding, unsupported by genuine inclusivity and authentic experiences, risks becoming a fragile empty facade, undermining IKN’s credibility as a global destination. The IKN project transcends a mere geographical shift; it's a significant political undertaking that, while reflecting governance ambitions, potentially imposes a hegemonic national identity, overlooking local cultural diversity and genuine community participation. Furthermore, our analysis indicates that the theoretically ideal Pentahelix collaboration model may devolve into an "elite vehicle" if power imbalances among government, business, academia, community, and media are not actively addressed, potentially marginalizing local voices. Enhanced connectivity, while crucial, could lead to "disaster rather than blessing" without robust capacity planning and strict tourism regulations, risking overtourism and ecological/cultural degradation. Economic opportunities are fraught with inequity risks, where benefits might concentrate among newcomers and large investors, while local communities face gentrification and social displacement. The success of East Kalimantan's tourism hinges on effective governance capable of overcoming fragmentation and conflicts of interest, ensuring urban branding reflects genuine local authenticity.